Association of Gut Microbial Clostridia With Brain Functional Connectivity and Gastrointestinal Sensorimotor Function in Patients With Irritable Bowel Syndrome, Based on Tripartite Network Analysis - Simrén, Magnus (University of Gothenburg, 2019)
Clinical study assessing the interactions among the brain, gut, and microbiota affect the pathophysiology of irritable bowel syndrome (IBS). Data comes from a larger study where the role of gut microbiota for symptoms in IBS is explored, including interactions with other pathophysiological factors. (Labus, J.S., Osadchiy, V., Hsiao, E.Y. et al. (2019) )

Data från vetenskaplig artikel (Labus, J.S., Osadchiy, V., Hsiao, E.Y. et al. (2019) ) med fokus på interaktion mellan tarmflora och hjärnan hos patienter med IBS (irritabel tarm) och friska kontrollpersoner; detta är del i ett större projekt som värderar tarmflorans betydelse vid IBS och hur denna samverkar med andra faktorer och kan leda till symtom hos patienter med IBS.
Association of Gut Microbial Clostridia With Brain Functional Connectivity and Gastrointestinal Sensorimotor Function in Patients With Irritable Bowel Syndrome, Based on Tripartite Network Analysis
Keywords: Irritable Bowel Syndrome; Irritabel tarmsyndrom; gut microbiota; tarmflora; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap; Clinical Medicine; Klinisk medicin; Gastroenterology and Hepatology; Gastroenterologi och hepatologi; Health; Hälsa